Creative Agency @Komunalab Overcoming Short Attention Spans in Food and Beverage Content Production - Putra, Ersya Gustika; Nurfalah, Farida; Hermawan, Abdul Jalil (PT FORMOSA CENDEKIA GLOBAL, 2025)
The phenomenon of short attention span on social media, perticularly Instagram, poses a significant challenge in the food and beverage industry. Users tend to have very limited attention time, which affects how they interact with promotional content. This research aims to examine the strategies employed by the creative agency @komunalab to address short attention spans in the production of food and beverage content on Instagram. The research method used is qualitative with a descriptive approach. Data was collected through observations, in-depth interviews with the founder and internal team of @komunalab, and related document studies. The research location is situated in the city of Majalengka, involving samples from the @komunalab team, as well as the Tsamie Noodle Bar dan Kedai Halaman restaurants. The result of this research indicate that @komunalab successfully implement various visual and narrative elements, such as the use of color symbolism and hook techniques in content, to capture audience attention. The produced content has consistently enchanced engagement and impression, demostrating the effectiveness of the strategies applied in confronting the challenges of short attention spans.